Book reviewed: De Westfalia a Cosmópolis. Soberanía, ciudadanía, derechos humanos y justicia económica global. Autores: Cortés Rodas, Francisco & Piedrahíta - Saldarriaga Madrigal, Andrés Eduardo (Estudios de Filosofía, 2011)
On some given night in the second century AD, Emperor Marcus Aurelius wrote what would later be known as his Meditations. In one of these fragments, he says the following: “If intellectual capacity is common to us, reason, why we are rational, is also common to us. If so, the reason that prescribes what we should do or not do is also common. If so, the law is also common. If so, we are citizens. If so, we participate in some kind of political constitution. If so, the world is like a city. Because what other common constitution would it be said that the entire human race participates in? And from there, from that common city, intellectual, rational and legal capacity also comes to us. Or from where?”